A unique colorimetric and ratiometric reversible fluorescent probe for HSO3−/H2O2 detection and imaging in real water samples, rice leaves and roots. (September 2022) - Wang, Jian; Li, Haoyang; Xu, Weibo; Zhang, Bo; Wang, Yu; Chen, Nan; Zhou, Qinghai; Ren, Tianrui
Abstract: A reversible colorimetric and ratiometric fluorescent probe (QG-Py ) was developed for HSO3 − detection. The probe showed large changes in absorbance and emission wavelength shift both with 155 nm when reacted with NaHSO3 . Furthermore, probe QG-Py exhibited high selectivity and sensitivity to NaHSO3 with quantitative analysis in real water samples through colorimetric and ratiometric methods. Interestingly, the reaction product (QG-Py-SO 3 H ) displayed structural recovery to QG-Py induced by H2 O2, accompanied with reversible optical properties. Probe QG-Py was established to visualize HSO3 − /H2 O2 in MCF-7 cells. Importantly, QG-Py was also successfully applied for HSO3 − /H2 O2 detection and imaging in rice roots and leaves, providing better understanding of the influence of SO2 derivatives to crops, as well as a new and simple method for evaluating environmental pollution of SO2 . Graphical abstract: Image 1 Highlights: Developed a colorimetric and ratiometric probe for bisulfite with reversible property. Quantitative analysis of HSO3 − in water samples by colorimetric and ratiometric methods. The probe QG-Py was applied to imaging HSO3 − /H2 O2 in MCF-7 cells. QG-Py was successfully applied to imaging bisulfite in rice tissues (leaves and roots).